PENGARUH ETOS KERJA, LINGKUNGAN KERJA DAN PENGAWASAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PT. SELOK JAYA JUWANA PATI - Susilowati Susilowati; Moch Slamet; M.D. Kharis Rifai (KINDAI, 2025)
This study aims to analyze the effect of work ethic, work environment, and supervision on employee work productivity, with job satisfaction as an intervening variable at PT Selok Jaya Juwana Pati. This research employed a quantitative approach using primary data collected through questionnaires distributed to 72 respondents. Data analysis was conducted using Partial Least Squares (PLS) to test the proposed hypotheses and relationships among variables. The results indicate that work ethic, work environment, and supervision have a positive and significant effect on job satisfaction. Furthermore, work ethic, work environment, and supervision also positively and significantly influence employee work productivity. Job satisfaction has a positive and significant effect on work productivity and serves as an intervening variable in the relationship between work ethic, work environment, supervision, and employee productivity at PT Selok Jaya Juwana Pati. Keywords: work ethic, work environment, supervision, employee satisfaction and work productivity